Cuina sense pares / Cooking without parents. (30th September 2020) - Bertran, M; Diaz, C; Garcia, T; Iglesias, M; Martinez, F; Polo, C; Puigdemont, I
Abstract: Issue: Health promotion in Catalunya isn't a mandatory competency for councils; hence fomenting healthy eating habits isn't a priority for many municipalities because they have to destiny the resources in required issues. To revert this situation, Barcelona Provincial Council, a second level local administration, gives both technical and economic support for health promotion which is specially needed for municipalities with fewer inhabitants. Description of the Problem: Adolescence implies autonomy to eat and often it turns in unhealthy eating habits. For this reason, Barcelona Provincial Council, in 2010 creates the project "Cuina sense pares" to promote a healthy eating and an optimum nutritional state from 14 to 18 teenagers in the province of Barcelona. The project counts on cooking workshops throughout territory and on a website www.cuinasensepares.cat that facilitates resources and cooking proposals adapted to the collective. Questions: What was the response of the municipalities in the project? How municipalities value the project? Has it been echoed in the media? Results: In 10 years, 673 workshops have been realised in 154 municipalities from the 311 in the province of Barcelona with a participation of 9.069 teenagers. Additionally, a 60% of the applicant municipalities have less than 10.000 inhabitants. The municipal technicians have rated the cooking workshops with an average of 9.11 among all. It has appeared 126 times in news media. In addition, the website has had more than 94.000 views and the Youtube channel has had 33.400. Lessons: Involve the young in their eating by the elaboration of easy and healthy recipes. As an innovation, healthy cooking workshops are offered to municipalities complemented by a website. Key messages: Facilitate tools to municipalities to boost healthy promotion eating programmes between the young. Foment a healthy eating between the young by attractive cooking proposals.